Understanding consumer’s cross-channel switching intention in the home appliances industry via push-pull-mooring framework - Chuah, Dennis Sing Ming (2022)
The internet has become ubiquitous in our daily lives, and e-commerce is increasingly important. The retail environment has transitioned from traditional single-channel retail to include multiple channels. The consumer’s cross-channel switching behaviour is a much-studied phenomenon. When the customers switch channels, they may also switch retailers.